OPTIMASI WAKTU PRODUKSI DAN PENGHAMBATAN BAKTERIOSIN DARI BAKTERI ASAM LAKTAT YANG DIISOLASI DARI AIR SUSU IBU (ASI) TERHADAP BAKTERI Escherichia coli ATCC 25922 - Ngurah Dwi Ariesta Wijaya Putra, AA.; Ekawati, I Gusti Ayu; Puspawati, Ni Nyoman (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2015)
Bacteriocin is an antimicrobial peptide that is produced by bacteria that kills or inhibits the growth of other bacteria. This study aims to determine the optimum time production of bacteriocin and determine the inhibitory of LAB bacteriocin isolated from breast milk to the bacterium Escherichia coli ATCC 25922. This study consists of three stages: the first is a confirmatory test, the second is the antimicrobial activity of Cell-free Supernatant (CFS) containing bacteriocins, and the third is a bacteriocin antimicrobial activity. Bacteriocin production was performed by incubating 9 isolates of LAB in various times of 12, 24, 36, 48, and 60 hours. Metabolites produced were tested for inhibitory by well-agar diffusion method. The positive results were continued with the isolation of bacteriocin and then re-tested for the inhibitors against Escherichia coli ATCC 25922. The research data was analyzed descriptively. Confirmation test results showed that the isolates of LAB and Escherichia coli used are suitable with the characteristics of the bacteria. The results of the antimicrobial activity of CFS containing bacteriocin showed that the B10b isolate has the highest inhibition with incubation time of 36 hours with the zone inhibition of 6.20 mm, and the B8 isolate has the lowest inhibition with incubation time of 48 hours with the zone inhibition of 0.10 mm. The results of the antimicrobial activity of bacteriocin showed that the B10b isolate has the highest inhibition with incubation time of 36 hours with the zone inhibition of 3.46 mm and the A1 isolate has the lowest inhibition with incubation time of 60 hours with the zone inhibition of 1.10 mm.
Keywords: bacteriocin, lactic acid bacteria, breast milk, Escherichia coli ATCC 25922